Legality of Transitioning Residential Homes for Online Business from the Perspective of Citizen’s Rights and Obligations - Kennedy, Alexander (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the legality of using residential homes for online businesses in Indonesia, focusing on the interplay between citizens' rights and obligations. Utilizing a Normative Juridical approach, it examines laws such as Law No. 1 of 2011 on Housing and Residential Areas, which allows limited business activities without compromising residential functions. Data highlights challenges such as noise, increased traffic, and waste management. The findings stress the need for balanced solutions through responsible business practices, adherence to regulations, and community dialogue. This research contributes to sustainable regulatory frameworks for home-based businesses, fostering harmony between economic activities and residential quality of life. Implications emphasize collaboration among stakeholders to achieve economic and social balance.